Effect of Bengkoang (Pachyrhizus erosus) Extract on Estrogen Receptor-?, Progesterone Receptor Expression, and Follicle-Stimulating Hormone Levels - Suryanti; Putri Ardela, Mayasari; Frenty Hadiningsih, Eka; Winarsih, Sri; Noorhamdani; Nurseta, Tatit; Norahmawati, Eviana (Indonesian Journal of Obstetrics and Gynecology, 2025)
Abstract Objective: Progesterone functions by inhibiting the release of Gonadotropin-Releasing Hormone (GnRH), which decreases Follicle-Stimulating Hormone (FSH) levels and converts them into hypoestrogens. This condition affects the expression of steroid, estrogen, and progesterone receptors, contributing to endometrial proliferation and secretion during the menstrual cycle. Methods: This study aims to demonstrate that Bengkoang extract administration increases the expression of Estrogen Receptor (ER), Progesterone Receptor (PR), and Follicle-Stimulating Hormone (FSH) in Wistar model rats. This study divided 25 female Wistar rats into five groups: one control group without progesterone and Bengkoang extract and four treatment groups injected with progesterone. After exposure, Bengkoang extract was administered to three treatment groups at doses of 70 mg/200 g BW/day (treatment 1), 140 mg/200 g BW/day (treatment 2), and 280 mg/200 g BW/day (treatment 3). Results: The results showed an increase in the expression of Estrogen Receptor- ? (Er?), Progesterone Receptor (PR), and Follicle-Stimulating Hormone (FSH) levels in treatment 1, treatment 2, and treatment 3 groups compared to the KP with p <0.05 Conclusion: The study investigating the effect of Bengkoang (Pachyrhizus erosus) extract on estrogen receptor-? (ER?), progesterone receptor (PR) expression, and follicle-stimulating hormone (FSH) levels has demonstrated significant findings. Keywords: Estrogen, Estrogen receptor-?, Follicle-stimulating hormone, Pachyrhizus erosus, Progesterone, Progesterone receptor